Pre-online information searching model of doctoral students: a grounded theory approach / Azree Ahmad - Ahmad, Azree (2015)
This study was conducted with the purpose of exploring the beginning stage in information searching process. As far as it is concerned, most would agree that information searching is a constructive and evolving process that has several stages. Based on few discoveries, pre-searching was found to have existed much earlier than the actual search or main interaction stage of the information searching process.However, not all users including doctor of philosophy (Ph.D.) degree students were successful in the beginning of their information searching. One way to look at this problem is to understand their pre-searching. The importance of pre-searching in information searching is that it has a significant impact on the quality of the search result. During the study, the data gathering activity involved a great length of doctoral students pre-searching experiences which were obtained through semistructured interview sessions. The selection of twenty three doctoral students as participants started with purposive sampling which was used to draw the first participant, while subsequent participants were selected based on theoretical sampling. Data was later transcribed and interpreted according to the coding paradigm of the grounded theory approach where emerging concepts were identified,arranged, linked and presented in a meaningful way. In addition, the constant comparative technique was also applied throughout the coding process which had helped to develop the emerging-theory. As a result, an inductive theory describing the pre-searching phenomenon had been constructed. In actual, the theory is based on five categories that had emerged during the analysis phase. The first two categories which are exploring and venturing explain doctoral students’ activities in relation tothe identification and retrieval activities of their research topics. Besides the two,another category named enriching shows how they would interact and learn from what they have retrieved from the first two categories. Another category known as ensuring describes how they would further enhance their learning and understanding process. The last category is engaging which enlightens doctoral students’ activities that are associated to the development of search terms that was used to engage presearching. Thus, this could also be seen as the earliest encounter in preparing a candidate search terms to be used later during the real information searching session.All emerging categories found in the present study are devoted in answering an area which before this has little explanation and understanding, hence is hoped to contribute to the body of knowledge and become the basis for future research.